ГЕФТИНАТ 250 — единственный в украине препарат нового поколения для терапии рефрактерного немелкоклеточного рака легкого (Iнститут експериментальної патології, онкології і радіобіології ім. Р. Є. Кавецького, 2008)
This paper offers the short review on chemotherapy schemes for treatment of non-small cell lung carcinoma (NSLC). Also, the data on randomized studies of geftinat usage for treatment of NSLC is presented.